Apoptotic regression of prostatic tissue induced by short-term doxazosin treatment in benign prostatic hyperplasia - (:unkn) unknown (My University, 2001)
OBJECTIVES: Benign enlargement of the prostate comprises both hypertrophy and in particular hyperplasia of prostatic stromal and glandular compartments. Alpha adrenergic blockade has been shown to be effective in the management of BPH. Recent investigations have shown that this effect may in part be due to apoptosis. METHODS: A total of 29 patients who were symptomatic due to BPH were enrolled into this prospective placebo controlled, double-blind randomized study and underwent prostatectomy at the end of the 4th week. Clinical efficacy was evaluated by a set of detailed investigations. Surgical specimens were analyzed by immunohistochemistry and tissue components of stroma, smooth muscle and glandular epithelium were calculated by a software on a computer after representative areas were scanned and captured as high resolution images. Apoptosis in each tissue specimen was analyzed by Terminal Deoxynucleotidyl Transferase End Labelling (TUNEL) method utilizing Biotin-16-dUTP. RESULTS: Both groups were similar in terms of baseline evaluation in all aspects. There was a steady decline in patients' urinary complaints as evidenced by International Prostate Symptom Score System (IPSS) in the doxazosin group compared to placebo. Uroflowmetric investigations on patients revealed that maximum flow rates in the active drug group increased throughout the study. Mean PSA levels decreased by 14% at the end of the study in the doxazosin group, while it increased by 11% in the placebo group. Average stroma to epithelial ratio in the doxazosin group was 2:1 in comparison to a value of 1:1 in the placebo group. The rate of apoptosis was 2.2% and 3.2% for the epithelial and stromal compartments, respectively, in the doxazosin group, and 1.2% and 2.7% for the placebo arm. CONCLUSIONS: These data suggest apoptosis as the possible underlying molecular mechanism partly responsible for the clinical efficacy and morphological changes induced by doxazosin treatment in BPH.
Keywords: Humans; Middle Aged; Aged; Male; Time Factors; Apoptosis; Double-Blind Method; Prospective Studies; Prostatic Hyperplasia; Adrenergic alpha-Antagonists; Doxazosin